Between daʿwa and Dialogue: Religious Engagement in Muslim-minority Environments - Ṿaisman, Yitsḥaḳ (Islam and Christian-Muslim relations, 2019)
Muslim engagement in interfaith and intercultural dialogue began in earnest after the turn of the twenty-first century in response to the rise of global jihad. Both dialogue and jihad are outgrowths of daʿwa, the call or mission of Islam, the principal mode of modern Islamic activism. The foundations were laid in the later part of the twentieth century by Muslim intellectual-activists living in non-Muslim environments, who played a special role in conceptualizing the new notion of dialogue and its relation to daʿwa. This essay focuses on four pioneering figures, two from the indigenous context of India - the modernist Asghar Ali Engineer and the reformist ʿālim Wahiduddin Khan, and two from the diaspora milieu of the West - the Palestinian-American academic activist Ismail Raji al-Faruqi and the European Muslim spokesman Tariq Ramadan. Each represents a distinct religious orientation that also reflects a different phase in the evolution of modern Islamic discourse. Taken together, these intellectual-activists chart the trajectory of modern Islam from the early pre-Islamist liberal hopes to the present post- and neo-Islamist efforts to navigate between Western-dominated globalization and Islamist jihadism.